(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the theoretical as well as the practical significance of bilingualism, aspects of language contacts characteristic of a particular era, making the right judgment about the causes of various types of linguistic phenomena in the context of studying a tertiary language. The basis of the study of the phenomenon of bilingualism is the need for contact between two or more languages, the need for linguistic contact among different nationalities, in the context of globalization processes taking place in the modern world, which entail the expansion of intercultural and interlanguage ties. Speech communication within the framework of close language contacts is of interest to various specialists, including linguists, psychologists, and teachers. Nowadays, the study of language contacts represents a very wide range of tasks that can be carried out at various levels, namely, sociological, political, cultural, economic, as well as linguistic.